OPTIMALISASI PERAWATAN DAN PEMELIHARAAN PERALATAN BONGKAR MUAT DI KAPAL SPOB MAHAKAM - Muhammad Idris; Rachmat Tjahjanto; Andi Anna Mutmainnah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the causes of the failure of the manual derrick system on the SPOB Mahakam vessel, which resulted in the suspension of cargo loading and unloading operations for 14 hours, and to evaluate the maintenance practices applied to cargo-handling equipment on board. The research method used was descriptive qualitative research through direct observation and interviews with ship officers and crew members. The findings indicate that the derrick failure was not only caused by the deterioration of structural conditions due to corrosion and material fatigue, but also by inadequate preventive inspections, insufficient maintenance documentation, and the predominance of reactive maintenance practices. In addition to the derrick, similar issues were identified in other equipment such as cranes, winches, cargo hoses, cargo pipelines, and other supporting cargo-handling components, indicating that the overall maintenance system has not yet been optimized. These findings highlight the need to implement a structured maintenance system based on a Planned Maintenance System (PMS), as well as to strengthen crew competencies in inspection, preventive maintenance, and equipment condition assessment prior to operations. Furthermore, spare-part procurement constraints were identified as a major obstacle to repairs, making it necessary to adopt a more proactive spare-parts logistics strategy through the establishment of minimum stock levels and the availability of critical components on board. With the implementation of a comprehensive PMS, enhanced technical training for crew members, and strong logistical support from the company, the effectiveness and safety of cargo loading and unloading operations can be significantly and sustainably improved.